Translingual English discrimination: Loss of academic sense of belonging, the hiring order of things, and students from the Global South - Dryden, Stephanie; Dovchin, Sender (2022)
Global North settings such as Australia are an attractive option for prospective students from the Global South to undertake tertiary studies. Using Linguistic Ethnography, we investigate the experiences that postgraduate students from the Global South have when studying in Australian university settings, to understand how translingual English discrimination affects them. We find that many students from the Global South encounter situations of translingual English discrimination, which affect their academic sense of belonging and the hiring order of things. Being penalised for their linguistic practises in their assignment work, or being provided with unclear and insufficient information during the early stages of their studies can both result in a loss of sense of academic belonging. These students may also be affected by the hiring order of things through additional barriers in gaining university employment due to perceptions that they have linguistic, work experience and qualification shortcomings, despite strong evidence to the contrary. We outline the implications of these forms of translingual English discrimination and recommend institutional changes to address these discriminatory actions.